Solvent Extraction of Chromium (VI) From Mineral Acid Solutions By Tributyl Amine - A.V.L.N.S.H. HARI HARAN; D.MURALI KRISHNA (International Journal of Pharma and Bio Sciences, 2010)
Chromium (VI) Considered as a serious health hazard and it has attracted attention as a pollutant in natural waters. The sources of contamination of chromium in natural waters and in the Environment are from electroplating, tanning industries and waste solution from oxidative dyeing and leaching from sanitary land – fills, In view of this the separation and determination of chromium has been receiving considerable attention. The extraction of Chromium (VI) from hydrochloric, sulphuric and nitric acid solutions with Tributyl amine (TBA) in chloroform has been studied. The optimum conditions for extraction were established from the study of the effect of several variables like concentration of extractant, metal ion, acidity etc. The extractions are nearly quantitative with all the acid systems. The extracted species are identified. The method has been applied for the recovery and determination of chromium in natural as well as industrial effluents.